2018
DOI: 10.1111/eci.12985
|View full text |Cite
|
Sign up to set email alerts
|

Obesity impairs leukocyte‐endothelium cell interactions and oxidative stress in humans

Abstract: Our findings reveal that endothelial dysfunction markers are altered in human obesity and are associated with proinflammatory cytokines and increased oxidative stress parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…In this context, mitochondrial membrane potential is critical for maintaining the physiological function, as it mediates the cell's capacity to generate ATP by oxidative phosphorylation. In fact, a decrease in the mitochondrial membrane potential may be linked to apoptosis (Lemasters et al., ), as has been shown in type 2 diabetes patients (Hernández‐Mijares et al., ), whereas an increase has been associated to a surplus nutrient supply, as we have recently demonstrated in obese patients (López‐ Domènech et al., ). However, in the present study we have not observed changes in mitochondrial membrane potential, suggesting that different underlying molecular mechanisms are involved in the PMNs dysfunction that characterizes different inflammatory‐related pathologies.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In this context, mitochondrial membrane potential is critical for maintaining the physiological function, as it mediates the cell's capacity to generate ATP by oxidative phosphorylation. In fact, a decrease in the mitochondrial membrane potential may be linked to apoptosis (Lemasters et al., ), as has been shown in type 2 diabetes patients (Hernández‐Mijares et al., ), whereas an increase has been associated to a surplus nutrient supply, as we have recently demonstrated in obese patients (López‐ Domènech et al., ). However, in the present study we have not observed changes in mitochondrial membrane potential, suggesting that different underlying molecular mechanisms are involved in the PMNs dysfunction that characterizes different inflammatory‐related pathologies.…”
Section: Discussionsupporting
confidence: 62%
“…A PMN suspension (1 × 10 6 cell/ml) in RPMI medium (Gibco; Thermo Fisher Scientific, Waltham, MA, USA) was drawn across a monolayer of HUVECs (flow rate 0.36 ml/min) and visualized by an inverted microscope (Nikon Eclipse TE 2000‐S; Minato, Tokyo, Japan) coupled to a video camera (Sony Exware HAD; Koeln, Germany). A five‐minute period of flow across a 5 × 25 mm portion of the coverslip was recorded and then used to evaluate rolling velocity, rolling flux, and adhesion, as described previously (López‐ Domènech et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, periodontitis and endothelial dysfunction have been shown to be closely connecting [20,21]. In line with this, we have shown in a previous study that the release of ROS from leukocytes is exacerbated in a proinflammatory state, thus contributing to oxidative stress and endothelial dysfunction in obesity and periodontitis [8,22]. Furthermore, we have demonstrated worse clinical outcomes in obese patients than in non-obese subjects after non-surgical periodontal treatment (at 3 months) [17], which is evidence of a negative effect of obesity on the response to periodontal treatment.…”
Section: Introductionsupporting
confidence: 72%
“…It would be advisable to study MDF and OS prevention by MNs in FA patients using biomarkers of mitochondrial function in plasma or blood cells from FA patients. We recommend-as it has been performed in other pathologies-the determination in white blood cells of mitochondrial OS-related enzymes like SOD2, the determination of the mitochondrial membrane potential from isolated white blood cells [136], or 8 hydroxy-deoxyguanosine as a marker of mitochondrial oxidative DNA damage [137]. It would be also advisable to determine well known markers of systemic OS in plasma samples as an indirect marker of mitochondrial impairment, such as the determination of the lipoperoxide biomarker malondialdehyde or calculation of the reduced/oxidized glutathione ratio, the most important antioxidant in mammalian cells (GSH/GSSG) in whole blood of patients [105,111].…”
Section: Clinical Determination Of Mitochondrial Dysfunctionmentioning
confidence: 99%